School Head’s Leadership Style and Teacher’s Performance - Dinglasa, Charleen C.; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study aimed to determine the relationship between the school head’s leadership style and the performance of teachers at Don Gregorio Evangelista Memorial School, Santa Catalina, Zamboanga City. Using the Multifactor Leadership Questionnaire (MLQ) to assess leadership styles and the Teacher Performance Rating Tool (TPRT) aligned with RPMS-PPST, the researcher gathered data from 120 teacher-respondents. Statistical treatment included mean, standard deviation, and Pearson’s r to measure correlation. School leadership significantly affects the quality of teaching and learning. This study focuses on how the leadership style of the school head influences teacher performance as school leadership is critical to the success of any educational institution. The leadership style of the school head can either inspire or hinder the professional performance of teachers. At Don Gregorio Evangelista Memorial School in Santa Catalina, Zamboanga City, the increasing complexity of the educational environment necessitates an understanding of the relationship between school leadership and teacher performance. The results indicated that transformational leadership was the dominant style, and teacher performance was generally very satisfactory. The findings revealed a significant positive correlation (r = 0.73, p < 0.05) between leadership style and teacher performance, supporting the importance of effective leadership in educational outcomes. The study concludes with recommendations for school heads to adopt more inclusive and supportive leadership practices to foster a positive teaching environment.